Vasili Milgichil performs two Raven myths - Tatiana Khelol; Liudmila Gileva; Anatoly Sorokin (Alexander King, 2013)
Vasili tells and acts out two Raven tales. One about Quikinyaqu and humpback salmon and the other about Kulyu's new drum. First in Parenskiy dialect, then provided less animated versions in Russian. Recorded in his living room. I started the audio a little bit late, missing the beginning of the Koryak, although all is on the video file. I added a few seconds of silence at beginning of this file to better align with video audio track. Profession: archivist. Grew up in Palana. Speaker's dialect of Koryak is possibly a mix of Chauchu and Mikina. Also fluent (listening, reading, some writing/speaking) in English and Japanese. Alutor level is elementary.